Optimization of damage repair with piezoelectric actuators using the Taguchi method - Shaikh, Abdul Aabid; Hrairi, Meftah; Jaffar Syed, Mohamed Ali (Gruppo Italiano Frattura, 2024)
Over the last two decades, piezoelectric actuators have emerged as a promising solution for structural repair. In this work, initially the stress intensity factor (SIF) estimation using the finite element (FE) approach at crack tips in aluminium 2024-T3 plates. Based on Taguchi’s L9 orthogonal array the FE simulation has been conducted. Later, this study uses the optimization method via the design of experiments to systematically evaluate the effect of various dimensions and material qualities, especially under the conditions of Mode-I crack propagation. It also investigated the complex interaction of factors impacting adhesive bonds, piezoelectric actuators, and aluminium plates, The study not only analyses the parameter relationships but also examines their controls, identifying those best aligned with primary objectives. This sensitivity enhances the piezoelectric actuator's efficacy and quality. The research determines an optimal parameter combination, developing active repair performance and establishing an essential SIF benchmark. This research explores the complex world of piezoelectric actuator-assisted repairs, providing a road map for better structural rehabilitation